2022
DOI: 10.3390/vaccines10050772
|View full text |Cite
|
Sign up to set email alerts
|

Potential for a Plant-Made SARS-CoV-2 Neutralizing Monoclonal Antibody as a Synergetic Cocktail Component

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a public health crisis over the last two years. Monoclonal antibody (mAb)-based therapeutics against the spike (S) protein have been shown to be effective treatments for SARS-CoV-2 infection, especially the original viral strain. However, the current mAbs produced in mammalian cells are expensive and might be unaffordable for many. Furthermore, the emergence of variants of concern demands the development of strategies to prevent mutant esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 66 publications
(101 reference statements)
1
20
0
Order By: Relevance
“…In an ELISA assay using the WA1/2020 RBD and p11D7 conjugated to horseradish peroxidase (HRP), we observed that CR3022 binding to the RBD abolished the ability of p11D7 to bind to the RBD, while several other EUA therapeutic mAbs (CB6, tixagevimab and cilgavimab) did not inhibit the binding of p11D7 to the RBD (Figure 5 ). This was the expected outcome for CR3022 and CB6, given that we have previously provided evidence of this (Jugler et al ., 2022 ), validating that p11D7 has at least a partially overlapping epitope on the RBD with CR3022 (a Class 4 mAb) but not with CB6 (also known as etesevimab, a Class 1 mAb). Similarly, the two mAbs, tixagevimab (also known as COV2‐2196, a Class 1/2 mAb) and cilgavimab (COV2‐2130, a Class 3 mAb) did not compete with the binding of p11D7 to the RBD.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…In an ELISA assay using the WA1/2020 RBD and p11D7 conjugated to horseradish peroxidase (HRP), we observed that CR3022 binding to the RBD abolished the ability of p11D7 to bind to the RBD, while several other EUA therapeutic mAbs (CB6, tixagevimab and cilgavimab) did not inhibit the binding of p11D7 to the RBD (Figure 5 ). This was the expected outcome for CR3022 and CB6, given that we have previously provided evidence of this (Jugler et al ., 2022 ), validating that p11D7 has at least a partially overlapping epitope on the RBD with CR3022 (a Class 4 mAb) but not with CB6 (also known as etesevimab, a Class 1 mAb). Similarly, the two mAbs, tixagevimab (also known as COV2‐2196, a Class 1/2 mAb) and cilgavimab (COV2‐2130, a Class 3 mAb) did not compete with the binding of p11D7 to the RBD.…”
Section: Resultsmentioning
confidence: 85%
“…The chimeric 11D7 transiently expressed in ΔXFT N. benthamiana plants peaked within a week after agroinfiltration to approximately 131 μg of p11D7 per gram of FLW. This level of expression is similar to other mAbs recently produced by our group using the same expression vector based on the geminiviral bean yellow dwarf virus (Jugler et al ., 2022 ) and allowed accumulation of milligram levels necessary for in vitro and future in vivo studies. However, this level of expression is lower than those of mAbs we produced using more optimized geminiviral vectors (Diamos et al ., 2020 ) or other plant‐made proteins such as griffithsin (GRFT) (Fuqua et al ., 2015 ) that have shown potent anti‐viral activity against SARS‐CoV‐2 (Alsaidi et al ., 2021 ; Palmer, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A table reporting neutralization potencies of nAbs obtained in plants and mammalian cells is presented ( Table 1 ). Differences in the IC values of the same antibody obtained either in plants or mammalian cells are evident for nAbs CA1 and CB6 (Jugler et al, 2022 ). In some cases, it is difficult to directly compare data between the publications due to differences in the IC calculations, but it is evident that mAbJ08-MUT produced both in plants and mammalian cells is the only nAb endowed with potencies in the 10 ng/mL range.…”
Section: Discussionmentioning
confidence: 99%